Weight‐for‐length trajectories in the first year of life in children of mothers with eating disorders in a large norwegian cohort. Issue 4 (30th April 2014) - Perrin, Eliana M.; Von Holle, Ann; Zerwas, Stephanie; Skinner, Asheley Cockrell; Reba‐Harrelson, Lauren; Hamer, Robert M.; Stoltenberg, Camilla; Torgersen, Leila; Reichborn‐Kjennerud, Ted; Bulik, Cynthia M.
ABSTRACT Objective To describe weight‐for‐length (WFL) trajectories in the children (birth‐12 months) of mothers with and without eating disorders. Method This study is based on the Norwegian Mother and Child Cohort Study (MoBa) conducted by the Norwegian Institute of Public Health. We categorized women (N = 57, 185) based on diagnosis prior to and during pregnancy: anorexia nervosa, bulimia nervosa, eating disorder not otherwise specified‐purging subtype, binge eating disorder, or no eating disorder. The primary analysis included a shape invariant model fitted with nonlinear mixed effects to compare growth rates across eating disorder subtypes. Results The children of mothers reporting any eating disorder had a lower WFL growth rate from birth to 12 months than the children of mothers without eating disorders, even after adjusting for relative birth weight and some confounders known to affect growth. Discussion In this cohort, child WFL was related to maternal eating disorder status before and/or during pregnancy. These differences in growth trajectories warrant further study of long‐term health outcomes and, if replicated, tailoring counseling to mothers with eating disorders during pregnancy. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:406–414)